2011
DOI: 10.1051/0004-6361/201015264
|View full text |Cite
|
Sign up to set email alerts
|

C-GOALS:Chandraobservations of a complete sample of luminous infrared galaxies from the IRAS Revised Bright Galaxy Survey

Abstract: We present X-ray data for a complete sample of 44 luminous infrared galaxies (LIRGs), obtained with the Chandra X-ray Observatory. These are the X-ray observations of the high luminosity portion of the Great Observatory All-sky LIRG Survey (GOALS), which includes the most luminous infrared selected galaxies, log (L ir /L ) ≥ 11.73, in the local universe, z ≤ 0.088. X-rays were detected from 43 out of 44 objects, and their arcsec-resolution images, spectra, and radial brightness distributions are presented. Wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
274
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 156 publications
(294 citation statements)
references
References 104 publications
(195 reference statements)
19
274
1
Order By: Relevance
“…It is interesting to notice that also the hardness ratio and the observed 2-10 keV luminosity inferred by Chandra are consistent with a large fraction of the objects of the sample of Iwasawa et al (2011;see Figures 5 and 6 of their paper, respectively), which might indicate that several more heavily obscured low-luminosity AGNs are present in LIRGs of the GOALS sample. Moreover, we have shown that in the low-count regime it is possible to miss obscured AGNs by adopting a simple phenomenological model to reproduce their X-ray spectra.…”
Section: Heavily Obscured Low-luminosity Agns In U/lirgssupporting
confidence: 67%
See 1 more Smart Citation
“…It is interesting to notice that also the hardness ratio and the observed 2-10 keV luminosity inferred by Chandra are consistent with a large fraction of the objects of the sample of Iwasawa et al (2011;see Figures 5 and 6 of their paper, respectively), which might indicate that several more heavily obscured low-luminosity AGNs are present in LIRGs of the GOALS sample. Moreover, we have shown that in the low-count regime it is possible to miss obscured AGNs by adopting a simple phenomenological model to reproduce their X-ray spectra.…”
Section: Heavily Obscured Low-luminosity Agns In U/lirgssupporting
confidence: 67%
“…For example, in a low-luminosity AGN the silicate absorption feature would be diluted by the strong IR continuum of the host galaxy. Iwasawa et al (2011) studied 44 LIRGs from the GOALS sample with Chandra and assessed the presence of an AGN using the hardness ratio HR H S H S ( ) ( ) º -+ , where H and S are the background-corrected counts in the 2-8 and 0.5-2 keV ranges, respectively. Sources with HR 0.3 > -are reported as candidate AGNs.…”
Section: Ir and X-ray Tracers Of Agn Activity In U/lirgsmentioning
confidence: 99%
“…Although these systems are relatively rare in the local universe, Le Floc'h et al (2005) have shown that high infrared luminosities may have been the norm at redshifts beyond 0.7. To understand these cosmically important objects and the physical processes that occur in them, the Great Observatory All-Sky LIRG Survey (GOALS; Armus et al 2009) team has compiled data across a number of different wavelength regimes, including Hubble Space Telescope imaging in the optical (Kim et al 2013) and near-infrared (Haan et al 2011), Chandra X-ray observations, (Iwasawa et al 2011), Spitzer spectra in the mid-infrared (Stierwalt et al 2013), GALEX observations in the near and far ultraviolet (Howell et al 2010), and Herschel Space Telescope spectra in the far-infrared (Díaz-Santos et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…tidal stream). This galaxy is classified as a star forming system based on observations in the optical (Veilleux et al 1995;Yuan et al 2010), mid-infrared (Lutz et al 1999;Risaliti et al 2006;Stierwalt et al 2013;Inami et al 2013), and X-ray (Franceschini et al 2003;Iwasawa et al 2011). This galaxy has been studied by several other authors to date, most finding evidence for outflows on a variety of scales.…”
Section: Introductionmentioning
confidence: 99%
“…The Chandra GOALS survey on the other hand comfortably detects X-rays over the Bird system (Iwasawa et al 2011), but the emission is soft, and extended, with the strongest concentration over the Head component, strongly suggesting SF rather than AGN origin. They do note some ambiguities with the galaxy regarding its morphology and a possibly elevated X-ray [SiXIII] emission line.…”
Section: Is There An Agn Hidden In the Bird?mentioning
confidence: 99%